Comparative evaluation of natural curcumin and synthetic chlorhexidine in the management of chronic periodontitis as a local drug delivery: A clinical and microbiological study - V Anitha; P Rajesh; M Shanmugam; B Meena Priya; S Prabhu; V Shivakumar (Wolters Kluwer Medknow Publications, 2015)
Background of the Study: The aim of this study is to evaluate the efficacy of natural curcumin in the management of chronic periodontitis as local drug delivery in comparison to synthetic chlorhexidine, which is the gold standard. Materials and Methods: Thirty chronic periodontitis patients with an age range of 20-50 years with probing pocket depth (PPD) of 4-6 mm were included. Curcumin and chlorhexidine gel was applied in the contralateral disease sites at baseline and day 15. The clinical parameters like PPD, clinical attachment level (CAL), gingival index (Loe and Silness) and plaque index (Turesky Gillmore modification of Quigley Hein) were recorded and colony forming units (CFU) were assessed microbiologically at baseline, 15 and 30 days. Results: There was a significant reduction of the clinical parameters (PPD, CAL) and microbiological parameters CFU at 15 and 30 days for both the groups. Curcumin group showed a greater reduction in the clinical parameters when compared with chlorhexidine group. Both groups had a significant reduction in parameters when compared with baseline. Conclusion: Although curcumin has equivalent benefit to chlorhexidine, curcumin being an ayurvedic herb is an excellent alternative to chlorhexidine due to minimal side-effects.